The Role of Good Corporate Governance (GCG) in Islamic Banking: An Analysis of Green Banking and Corporate Social Responsibility Practices at BSI KCP Sokaraja - Aflah Maula Firdaus; Safrina Muarrifah; Naerul Edwin Kiky Aprianto (Wealth: Journal of Islamic Banking and Finance, 2026)
The transformation of the global banking industry is increasingly emphasizing environmental sustainability and social responsibility, particularly in response to the climate crisis and poverty. As part of the Islamic banking sector, BSI seeks to integrate Good Corporate Governance (GCG) principles into its operations to support green banking and Corporate Social Responsibility (CSR) practices. This study aims to analyze the role of GCG in driving the implementation of green banking and CSR, as well as its impact on banking performance. The research objectives include evaluating the policies, programs, and challenges associated with the application of sustainable practices at BSI KCP Sokaraja. This study employs a descriptive qualitative approach, utilizing data collection methods such as observation, in-depth interviews, and document analysis. The research subjects include BSI KCP Sokaraja employees involved in banking operations, namely the Branch Manager, Branch Operation Supervision Manager (BOSM), and Back Office staff. Data were analyzed through data reduction, data presentation, and conclusion drawing. Data validity was tested using source and technique triangulation to ensure the credibility and reliability of the findings. The findings reveal that BSI KCP Sokaraja has implemented four out of six green banking indicators. The role of GCG has proven significant in supporting transparency, accountability, and compliance with Sharia principles in green banking and CSR practices. However, this study is limited by its focus on a single branch office, meaning the findings cannot be broadly generalized. Future research is recommended to expand the scope to other branches, quantitatively examine the impact of green banking and CSR on the bank's financial performance, and further explore the alignment of Sharia principles with sustainability practices.